1901 Mich. Pub. Acts 154, § 24, pt. 10. - (:unkn) unknown (My University, 1901)
Local Acts, no. 344, tit. 7, § 24, pt. 10: [T]o direct the location of slaughter houses, markets and buildings for the storing of gunpowder and other combustible and explosive substances[.]
Keywords: GUNPOWDER - STORAGE